Implementasi Program Rumah Padat Karya di Kecamatan Lakarsantri Kota Surabaya: Studi Kasus pada Unit Usaha Pitstop Kelurahan Lidah Kulon - Lily Aisya Putri; Rosdiana, Weni (Perspektif Administrasi Publik dan hukum, 2026)
The Labor-Intensive Housing Program is one of the Surabaya City Government’s policies aimed at reducing poverty and unemployment through labor-intensive community empowerment. This study aims to describe and analyze the implementation of the Labor-Intensive Housing Program (RPK) at the Pitstop business unit in Lidah Kulon Village, Lakarsantri Subdistrict, Surabaya City. This study employs a qualitative method with a descriptive approach, utilizing Van Meter and Van’s policy implementation theory. Primary data were collected through interviews and observations, while secondary data were derived from official documents and relevant publications. The results showed that the implementation of the Pitstop Labor Intensive Housing Program has not yet been optimal. In terms of policy standards and objectives, the program’s goals have been clearly defined but have not yet been fully achieved. Regarding resources, the availability of facilities and funding is adequate, but there are still limitations in human resources, particularly skilled technicians in the automotive repair field. Inter organizational communication has taken place but has not been intensive enough to support business sustainability. Characteristics of the implementing agents indicate that the structure of the Labor-Intensive Housing team has been clearly defined; however, implementation in the field has not been optimal due to weak coordination and communication. Economic, social, and political conditions-such as a less-than-strategic business location and high competition from similar businesses-have also contributed to the low number of customers. Meanwhile, the disposition of the implementers demonstrates a positive attitude in supporting the Labor-Intensive Housing program. The Labor-Intensive Housing Program must be supported by professional mechanics through education, certification, and collaboration with the private sector and training institutions to ensure the quality of services. In addition, building public trust, coordination among stakeholders, and intensive support through monitoring and evaluation are key to the success and sustainability of the Labor-Intensive Housing Program.